The Relationship between Body Mass Index and Hematological Parameters in Adult Female Students of Peshawar Medical and Dental College - Tahir, Maryam; Khattak, Hira Ehsan; Kamran, Jaleel; Sameer Hanif, Muhammad; Ghulab, Usama; Usman, Syed Ahmad (Journal of Neonatal Surgery, 2025)
Background: Obesity has become increasingly prevalent globally, associated with chronic inflammation, which contributes to conditions like atherosclerosis and metabolic syndrome. Hematological parameters (such as Hemoglobin, Hematocrit, RBC, WBC, and Platelets) are indicative of physiological status and could potentially correlate with obesity. Objective: To determine how BMI categories relate to hematological parameters in young female medical and dental students. Methodology: Study Design: Cross-sectional study conducted at Peshawar Medical and Dental Colleges from July to December 2022. Population: Female students aged 18-25 years, totaling 231 participants, chosen by convenience sampling. Procedure: After informed consent, participants completed a questionnaire, and anthropometric assessments (height and weight) were conducted to calculate BMI. Blood samples were collected and analyzed for hematological parameters. Statistical Analysis: Data was analyzed using SPSS version 21, with p-values <0.05 considered significant. Results: The study sample had a mean age of 21.83 ± 1.41 years, with an average height of 165.48 ± 4.88 cm and mean weight of 62.16 ± 8.26 kg. The mean BMI was calculated as 22.78 ± 3.54 kg/m². The mean Hemoglobin and Hematocrit levels were both 12.89 ± 1.15. The mean Red Blood Cell (RBC) count was 4.42 ± 0.38, White Blood Cell (WBC) count was 9007.88 ± 1710.79, and the mean Platelet count was 237476.19 ± 77515.21. Conclusion: Significant differences were found between BMI categories and Hemoglobin (Hb), Hematocrit (HCT), WBC, and Platelets. RBC did not show significant association. Higher BMI is linked to lower levels of Hemoglobin and Hematocrit. Strong positive correlations were observed between BMI and WBC as well as Platelet count.